2002
DOI: 10.1103/physrevb.65.193404
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature interface structure ofCaF2/Si(111)studied by combining x-ray standing waves with component-resolved photoemission

Abstract: X-ray photoelectrons excited by x-ray standing waves ͑XSW͒ are used to study the atomic structure of the low-formation-temperature (370°C) interface between CaF 2 and Si͑111͒. The core-level shift of the photoemission spectra of the Ca atoms at the CaF 2 /Si interface is used to distinguish interface Ca atoms from atoms in other ͑bulk͒ layers in the XSW measurements. Therefore, we obtained quantitative structure information specific to the buried CaF 2 /Si interface avoiding some of the ambiguities of XSW. Eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…28 On the other hand, our result matches well the interface distance of 251 pm determined by XSW for deposition of 1.7 TL CaF 2 at 370°C. 29 Therefore it seems that additional CaF 2 on top of the CaF interface layer increases the interface distance because of the attractive interaction between CaF interface layer and the CaF 2 layers of the film on top.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 On the other hand, our result matches well the interface distance of 251 pm determined by XSW for deposition of 1.7 TL CaF 2 at 370°C. 29 Therefore it seems that additional CaF 2 on top of the CaF interface layer increases the interface distance because of the attractive interaction between CaF interface layer and the CaF 2 layers of the film on top.…”
Section: Discussionmentioning
confidence: 99%
“…28 Klust et al showed by means of XSW that Ca also adsorbs on T 4 sites for low deposition temperatures. 29 The formation of a CaF interface layer due to dissociation of CaF 2 at the Si͑111͒ surface and subsequent desorption of SiF x complexes has also been verified by x-ray photoelectron spectroscopy. 30,31 Furthermore, investigations by grazing incidence x-ray diffraction ͑GIXRD͒ verified both T 4 and H 3 adsorption sites for ultrathin CaF films if they are treated by rapid thermal annealing at very high temperatures after deposition.…”
Section: Introductionmentioning
confidence: 97%
“…In order to produce the optical multilayer and filters, CaF 2 can be deposited as thin films using mainly physical vapor deposition (PVD) techniques such as, electron-beam evaporation (EBE) [6][7][8][9], thermal evaporation [10][11][12], r.f. magnetron sputtering [13], pulsed laser deposition (PLD) [14,15], and molecular beam epitaxial (MBE) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Physical vapor deposition techniques have been primarily used for the preparation of CaF 2 thin films. Some of these are molecular beam epitaxy, electron beam evaporation (EBE), thermal evaporation, radio frequency magnetron sputtering, etc. Understanding the surface growth of thin films is of both theoretical and practical interest.…”
Section: Introductionmentioning
confidence: 99%